: - Husin, Umar (Faculty of Law, University of Mataram, 2025)
The rapid advancement of technology has led to numerous innovations that ease human life. Among these, one of the most attention-grabbing developments is the emergence of artificial intelligence (AI). While AI brings a multitude of benefits, its presence also raises various legal issues, particularly in the context of corporate operations. In Indonesia, a company named PT Suryadhamma Investama has employed artificial intelligence to serve as a director, handling administrative tasks and participating in decision-making processes. Normatively (das sollen), this situation creates ambiguity concerning the legal accountability of a director that is an AI, as AI cannot be recognized as a legal subject due to its failure to meet the criteria of legal personhood. Consequently, AI lacks the legal standing to bear legal responsibility. Furthermore, AI cannot be sued or held legally liable because it is not classified as a legal subject under current legal frameworks. Empirically (das sein), this reality further obscures the normative provisions in place. On one hand, an AI-based director can assist companies in making various decisions; on the other hand, it challenges the certainty of legal accountability. Therefore, this study seeks to further elaborate the scope of liability associated with the use of artificial intelligence in corporate operations. The central legal issue explored in this research concerns the regulation of artificial intelligence’s legal liability in the management of a limited liability company under Law Number 40 of 2007 on Limited Liability Companies.The research method employed is normative juridical, utilizing statutory, conceptual, and case approaches.